Spectrochemical, EXAFS and Studies of Co(II), Ni(II) and Cu(II) Complexes of Thioglycolanalide - Bhagwat, V.W.; Nahar, P.C.; Mishra, Ashutosh; Choube, Ajit (Asian Journal of Chemistry, 2010)
Complexes of Co(II), Ni(II) and Cu(II) with thioglycolanalide (TGA) have been synthesized. Analytical studies show a 1:2 (M:L) stoichiometry for Ni(II) and Co(II) complexes while for copper the stoichiometry is found to be 1:1 and copper is present in the complex in Cu(I) state. The electronic spectral studies suggest octahedral geometry for Co(II) and Ni(II) complexes and is supported by EXAFS and XANES. Infrared studies indicate bonding through >C=O and —SH groups.